Republic of Armenia : Staff Report for the 2004 Article IV Consultation, Sixth Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines Armenia's 2004 Article IV Consultation, Sixth Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. Armenia's strong economic performance has been continuing in 2004. In January-September, the year-over-year rate of GDP growth was 10 percent, fueled by increases in agricultural production, housing construction, and services. Since mid-2003, banking sector performance has improved, and there has been a gradual return of confidence toward banks following the resolution of eight intervened banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet